Late Quaternary landscape reconstruction and geochronology in the northern Pampas of Buenos Aires province, Argentina - Zárate, Marcelo Arístides (2009)
This paper reports the main sedimentary characteristics, soil micromorphology and optically-stimulated luminescence (OSL) ages, and details the pedosedimentary reconstruction, of the Hudson site situated in the northern Pampas of Buenos Aires province. It also provides the OSL chronology and a reinterpretation of previously reported micromorphological features for the nearby site of Gorina. Finally, the stratigraphic records of both sites are compared and the main environmental events discussed in a regional context. At Hudson, situated at a low altitude environment close to the coastal plain, the basal fine-grained paludal deposits were unconformably covered by coastal marine sediments with an OSL age of ca. 128 ka supporting its correlation with the high stand of sea level of marine isotope stage 5e. A paleosol developed on the marine deposits and the underlying paludal sediments. OSL ages suggest that soil development and its subsequent erosion occurred over some period between ca. 128 and 54 ka. Fine sediment accumulation in a paludal environment continued until prior to ca. 23 ka when the accumulation of the uppermost loess mantle started. It continued until the early Holocene when present soil development began. At Gorina, OSL ages suggest that the upper part of the pedocomplex formed at some stage between ca. 194 and 56 ka. Loess then accumulated followed by an erosional phase; loess deposition restarted by ca. 29 ka and continued until the beginning of the Holocene (ca. 9 ka) when the present land surface was established. The stratigraphic and paleoenvironmental differences exhibited by the Hudson and Gorina records result from their contrasting geomorphological settings. The OSL geochronology suggests that the last interglacial (MIS 5) at Hudson is marked by the accumulation of marine deposits (MIS 5e) and the subsequent development of a paleosol. The equivalent soil-forming interval at Gorina is represented by the upper part of the buried pedocomplex. Both at Gorina and Hudson, loess accumulation was dominant especially during MIS 2. Loess accumulation continued during MIS 1 until the early Holocene with apparently somewhat higher sedimentation rates in Hudson. Pedogenesis has been predominant during the rest of the Holocene, resulting in the formation of the surface soil profiles.